2002
DOI: 10.1161/01.hyp.0000016179.52601.b4
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor Gene Transfer Downregulates Angiotensin II Type 1a Receptor in Vascular Smooth Muscle Cells

Abstract: Two distinct subtypes of angiotensin (Ang) II receptors, type 1 (AT(1)) and type 2 (AT(2)), have been identified. Vascular smooth muscle cells (VSMCs) usually express AT(1) receptor. To elucidate the direct effects of the AT(2) receptor on the AT(1) receptor in VSMCs, we transfected AT(2) receptor gene into cultured rat VSMCs. Overexpression of AT(2) receptor significantly decreased expression of AT(1a) receptor at both the mRNA and protein levels in the presence and absence of Ang II in VSMCs. Overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 25 publications
0
48
1
Order By: Relevance
“…27 Numerous studies have demonstrated that angiotensin II through AT1 receptor induces VSM cell proliferation and hypertrophy and has an essential role in extracellular matrix expansion. [29][30][31][32] Furthermore, Candesartan and cavernous tissue in SHR JE Toblli et al cell culture, animal models and clinical studies have supported the idea that AT1 receptor activation causes vascular superoxide release in vitro and in vivo leading to impairment of endothelium-dependent vasodilation. 33,34 In agreement with these findings, inhibition of AT1 receptor activation by AT1 receptor antagonist or ACE inhibitors improves endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…27 Numerous studies have demonstrated that angiotensin II through AT1 receptor induces VSM cell proliferation and hypertrophy and has an essential role in extracellular matrix expansion. [29][30][31][32] Furthermore, Candesartan and cavernous tissue in SHR JE Toblli et al cell culture, animal models and clinical studies have supported the idea that AT1 receptor activation causes vascular superoxide release in vitro and in vivo leading to impairment of endothelium-dependent vasodilation. 33,34 In agreement with these findings, inhibition of AT1 receptor activation by AT1 receptor antagonist or ACE inhibitors improves endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Although we cannot completely rule out that our results are a nuance of receptor overexpression, such an idea (ie, constitutive activity of the AT 2 receptor) has precedence. 31,[42][43][44][45] For example, the AT 2 receptor displays ligand pharmacology consistent with it residing in a constant, active conformation. 43 This receptor induces apoptosis in the absence of Ang II stimulation, and the AT 2 receptor antagonist PD123319 does not modulate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…43 This receptor induces apoptosis in the absence of Ang II stimulation, and the AT 2 receptor antagonist PD123319 does not modulate this effect. 31 In addition, Jin et al 44 showed that overexpression of the AT 2 receptor downregulates AT 1 receptor expression in vascular smooth muscle cells, with and without Ang II stimulation. In contrast to the AT 1 receptor, in which signal transduction pathways are well documented, the extent and type of intracellular signals that emanate from the AT 2 receptor have been difficult to define.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the different Ang II receptors can influence each other. [36][37][38][39][40] To exclude the possibility that the lack of one of the receptor subtypes alters the properties of the remaining receptors, we also investigated the effects of Ang-(1-7) in mice lacking all three Ang II receptor types. Although Ang-(1-7) was not able to reduce absolute MAP in the hypotensive triple KO mice, the percent changes induced by Ang-(1-7) were comparable with that in WT mice.…”
Section: Impact Ofmentioning
confidence: 99%